APLIKASI KAMUS IRREGULAR VERBS BERBASIS ANDROID - Anom, Dang; Danuri, Danuri; Jaroji, Jaroji (Politeknik Negeri Cilacap, 2018)
Irregular is verbs on English do not add with ed or d but change agree with rule. To listen andcomprehend only memorize from verb base make past tense and past participle. Because this resultmany people so think difficult in learning English specially of irregular verbs. Aim of this research is to make application dictionary irregular verbs base android to make support in listen English specially irregular verbs. Scheme of system use Unified Modelling Language, java programming and sqlite database. This research produce a application dictionary irregular verbs to use device mobile base android